A Comparative study of factors effecting Occupational Stress among Medical and Paramedical Staff in Public and Private Hospitals in Punjab - Satwinderjit Kaur, Nidhi Aggarwal, Ruhani Sohal, (European Economic Letters (EEL), 2024)
Out of the various resources involved in the production process (i.e, human and non-human), the human resources can utilize other production factors. Performance of employees determines the organization's growth and survival in all forms of service, industrial, and business organizations. In the present research, an attempt has been made to conduct a comparative analytical study relating to occupational stress level among medical and paramedical staff in public and private hospitals in Punjab. It has been recognized that health sector employees are among the highest groups subjected to work stress. From this analysis, it could also be inferred that public and private health workers expressed high degree of stress especially for Role Overload, Role Conflict, Political Pressure and Role Ambiguity .